Visualisation of autonomouos vehicle interior in virtual reality - Rizov, Tashko; Jankovic, Aleksandar; Tashevski, Risto; Angeleska, Elena (Serbian Society for Geometry and Graphics (SUGIG) Faculty of Mechanical Engineering, University of Belgrade, 2023)
In this paper we present the visualisation process of autonomous vehicle interior using virtual reality (VR). Autonomous vehicles are providing designers with more freedom in the design, since some traditional elements like driver position and controls are not needed. In addition, the autonomous vehicles are usually envisioned as a form of urban public transport in the future, meaning their interior should be designed to accommodate several passengers. The use of 3D models and renders is suitable for presenting the design of the interior of these vehicles, but the sense of space volume and ergonomics are not well presented. Using VR, we can provide full immersion of the user, providing the ability to completely visualize the interior of the vehicle. In addition, using game engines we are able to provide a complete virtual experience of the autonomous ride in an urban environment. In that way, visualisation in VR could be used to verify the design methodology utilized in the design process and verify the utilized interior design ergonomic standards.